The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.energyfuels.2c02713
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Prediction of Production Loss in Heterogeneous Tight Gas Reservoirs Using Dynamic Threshold Pressure

Abstract: Tight gas reservoirs commonly exhibit complex pore throat structures. Conventionally, a constant threshold pressure gradient (TPG) has been used to predict the production loss that arises from overcoming the rock's disinclination to flow water and gas through such complex pore throat structures. In this work, we find that the TPG is not constant during the production lifetime of a reservoir. The TPG varies significantly with both effective stress and water saturation, leading us to rename TPG as dynamic thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…As for the influence of the TPG on the productivity of tight gas reservoirs, these studies mainly utilize vertical well models to calculate gas productivity, and the productivity model of fractured horizontal wells with the TPG, including gas–water two-phase flow effects, is rarely reported. For instance, Tian et al obtained the TPG correlation by considering the influences of permeability, connate water, movable water, and vertical well models that accounted for the TPG, slip, and diffusion effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the influence of the TPG on the productivity of tight gas reservoirs, these studies mainly utilize vertical well models to calculate gas productivity, and the productivity model of fractured horizontal wells with the TPG, including gas–water two-phase flow effects, is rarely reported. For instance, Tian et al obtained the TPG correlation by considering the influences of permeability, connate water, movable water, and vertical well models that accounted for the TPG, slip, and diffusion effects.…”
Section: Introductionmentioning
confidence: 99%
“…Zafar et al 25 introduced two new TPG correlations based on the pore pressure and permeability and the pore pressure and water saturation. Wang et al 26 showed that the TPG varies significantly with both effective stress and water saturation, and a constant TPG approach underestimates production loss. Dong et al 27 established a dynamic pseudothreshold pressure gradient (PTPG) and showed that the vertical well performance considering dynamic PTPG was smaller than that of Darcy flow but larger than that of conventional non-Darcy flow.…”
Section: Introductionmentioning
confidence: 99%
“…Wang (2022)'s experimental results indicated that under water conditions, seepage in tight gas reservoirs exhibits nonlinear characteristics and forms the TPG. The TPG for the gas phase has a close power-law relationship with water saturation [32]. For the water-producing gas wells in water-bearing-inclined gas reservoirs considering stress sensitivity, Fu (2022) has developed a new gas well production equation that accurately determines the relationship between gas well production and stress sensitivity and water production [33].…”
Section: Introductionmentioning
confidence: 99%